Some additional records to the inventory of dragonflies and damselflies (Odonata) in Andalas University’s Limau Manis campus complex, Padang, West Sumatra - MUHAMMAD NAZRI JANRA; HENRY HERWINA (Universitas Syiah Kuala, 2020)
Since the publication of inventory list for dragonflies and damselflies within the boundary of Andalas University’s Limau Manis Campus Complex, Padang, on 2018, the survey efforts have been continuously conducted. Hence, in this article we add five odonate species new for Andalas University’s Limau Manis Campus Complex, with one species Drepanosticta cf. bispina may require further investigation and elaboration on its existence in West Sumatra. We also corrected the identification of Heliocypha fenestrata into H. angusta angusta. With this addition, Andalas University’s Limau Manis Campus Complex currently resides for 32 species and 9 families of Odonata, increasing from previously 27 species and 8 families.